Algunas observaciones sobre la variabilidad del componente verbal en unidades fraseológicas españolas - Szałek, Jerzy (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The article assesses the degree of variability of the verb component in Spanish phraseological units. The employment of the phraseological approach in connection with the semantic-pragmatic approach analysis and an attempt to present a gradation of selected synonymous units from the point of view of both idiomaticity and stability, serve as a basis for obtaining indispensable information in the process of constructing entries for the phraseological dictionary.
Some comments on the variability of the verb component in Spanish phraseological units